Sоciо-Ecоnоmic Wаys tо Imprоve the Well-Being of the Pоpulаtiоn - Shаvqiev, Erkin; Bоbоkulоv, Sаnjаr B. (Academia Open, 2025)
General Background: Socio-economic disparities remain a pressing concern in many transitional economies, including Uzbekistan. Specific Background: Despite sustained economic growth, challenges such as income inequality, limited social protection, and regional development imbalances persist. Knowledge Gap: Prior studies have predominantly focused on macro-level welfare indicators without adequately assessing the impact of integrated digital and policy reforms on equitable growth. Aims: This study aims to evaluate the effectiveness of government-led socio-economic strategies in enhancing population well-being through digitalization, fiscal reform, and targeted employment initiatives. Results: Employing a qualitative methodology enriched with statistical abstraction and systemic analysis, the findings reveal a consistent rise in per capita income, albeit with persistent urban–rural disparities. Targeted programs—including digitalized social assistance, vocational training, and small enterprise support—have demonstrably contributed to poverty reduction and improved living standards. Novelty: The study uniquely integrates digital reform analysis with socio-economic policy evaluation, offering a comprehensive perspective on reform-driven equity enhancement. Implications: The results suggest that sustainable improvements in well-being require a cohesive policy framework emphasizing public investment, governance transparency, and inclusive economic practices. Highlights : Integrated Reforms Work – Combining digitalization with fiscal and employment policies boosts income and reduces poverty. Urban–Rural Disparity Persists – Income growth is uneven, with rural areas lagging behind urban centers. Policy Coordination Is Key – Sustainable well-being relies on transparent, inclusive, and well-aligned public strategies. Keywоrds : Income Inequality, Digital Reforms, Social Protection, Regional Development, Poverty Reduction